Effect of metal salts on α-amylase-catalyzed hydrolysis of broken rice under a moderate electric field. (November 2020) - Li, Dandan; Huang, Yi; Tao, Yang; Xu, Enbo; Zhang, Rongguang; Han, Yongbin
Graphical abstract: Highlights: Metal salt could alter electro-assisted enzymatic hydrolysis of broken rice. Metal salt affected the hydrolysis mainly by altering α-amylase activity. Interactions between starch and metal ion showed no effect on the hydrolysis. Ca 2+ and Mg 2+ showed more positive effects on the hydrolysis than Mn 2+ and Cu 2+ . Abstract: This study aimed to evaluate the effects of metal salts on α-amylase-catalyzed hydrolysis of broken rice under a moderate electric field (MEF) by monitoring changes in hydrolysis efficiency, temperature, α-amylase activity, starch-metal ion interaction, and the structural and physicochemical properties of hydrolysates. Results showed that metal salts affected the hydrolysis mainly by altering α-amylase activity rather than by inducing thermal effect or interacting with starch. Reducing sugar content reached 125.0 g/L, while α-amylase activity increased by 18.16% when treated with 0.12 mmol/L Ca 2+ . Holes on hydrolysates treated with Ca 2+ and Mg 2+ were larger than those treated with Mn 2+ and Cu 2+ . No M–O bond was formed after the hydrolysis. The crystallinity was slightly increased with the hydrolysis and the values for Ca 2+ - and Mg 2+ -treated samples were larger. The water and oil absorption capacity of the hydrolysate treated with Ca 2+ was the highest. This study extended the knowledge of the roles of metal ions on MEF-assisted enzymatic hydrolysis and will contribute to the development of an innovative technology for starch modification.